Theological and sociological perspective of the social integration of refugee population - Ares, Alberto; Iglesias, Juan (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The article addresses the question of the social integration of the refugee population from a theological and sociological perspective. In its first part, the article focuses on the main theological aspects of forced migration, emphasizing the relevance of migration as sign of the times, and entering into a brief conceptualization of migration from the biblical tradition. Next, it focuses on synthesizing the contributions that the theological tradition makes to the concept of social integration. In its second section, the article lists the main characteristics of the concept of social integration from a sociological perspective, and then to analyze both the reception and integration system and the subsequent sociolabor incorporation of the refugee population in Spanish society.
Keywords: integration; forced migration; refugee; reception and policies